Three-dimensional flagella structures from animals’ closest unicellular relatives, the Choanoflagellates - Pinskey, Justine M; Lagisetty, Adhya; Gui, Long; Phan, Nhan; Reetz, Evan; Tavakoli, Amirrasoul; Fu, Gang; Nicastro, Daniela (eLife, 2022)
In most eukaryotic organisms, cilia and flagella perform a variety of life-sustaining roles related to environmental sensing and motility. Cryo-electron microscopy has provided considerable insight into the morphology and function of flagellar structures, but studies have been limited to less than a dozen of the millions of known eukaryotic species. Ultrastructural information is particularly lacking for unicellular organisms in the Opisthokonta clade, leaving a sizeable gap in our understanding of flagella evolution between unicellular species and multicellular metazoans (animals). Choanoflagellates are important aquatic heterotrophs, uniquely positioned within the opisthokonts as the metazoans’ closest living unicellular relatives. We performed cryo-focused ion beam milling and cryo-electron tomography on flagella from the choanoflagellate species Salpingoeca rosetta. We show that the axonemal dyneins, radial spokes, and central pair complex in S. rosetta more closely resemble metazoan structures than those of unicellular organisms from other suprakingdoms. In addition, we describe unique features of S. rosetta flagella, including microtubule holes, microtubule inner proteins, and the flagellar vane: a fine, net-like extension that has been notoriously difficult to visualize using other methods. Furthermore, we report barb-like structures of unknown function on the extracellular surface of the flagellar membrane. Together, our findings provide new insights into choanoflagellate biology and flagella evolution between unicellular and multicellular opisthokonts.
Keywords: Salpingoeca rosetta; choanoflagellate; flagella; cryo-electron tomography; vane; opisthokont evolution